2009
DOI: 10.1902/jop.2009.080594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Implant Loss and the Influence of Associated Factors

Abstract: The inserted implants showed a high survival rate, especially after the first year of insertion, even though the subjects were not maintained by specialists. All late implant losses were preceded by an early loss. Implant loss was significantly associated with smoking and periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 24 publications
3
73
1
7
Order By: Relevance
“…Investigators in several implant outcome studies reported that previous or present periodontitis was associated with an increased risk of implant failure, 15–19 a risk that can be decreased with successful periodontal treatment and maintenance therapy. 20 Although only 28 percent of the implants in our study were placed immediately after tooth extraction, immediate placement was associated with an increased risk of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in several implant outcome studies reported that previous or present periodontitis was associated with an increased risk of implant failure, 15–19 a risk that can be decreased with successful periodontal treatment and maintenance therapy. 20 Although only 28 percent of the implants in our study were placed immediately after tooth extraction, immediate placement was associated with an increased risk of failure.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Interest in the impact of local factors on implant survival has additionally been the focus of many reports that identify bone quality and quantity, as well as implant stability data. [7][8][9] However, given such a low incidence of device failure, it can be appreciated that large numbers of implants should be followed for long periods of time to best discern meaningful associations.…”
Section: Commentary and Analysismentioning
confidence: 99%
“…Few studies (5)(6)(7)(8)(9)(10)(11) analyze early failure of implants and study the related risk factors. Other studies (12)(13)(14)(15), specify the number of early and late failures, and indicate the risk factors related with the total number of failures. In these studies early failure rates vary from 1.2 to 3% and late failure rates from 0 to 1.8%, early failures being more frequent than late (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (12)(13)(14)(15), specify the number of early and late failures, and indicate the risk factors related with the total number of failures. In these studies early failure rates vary from 1.2 to 3% and late failure rates from 0 to 1.8%, early failures being more frequent than late (12)(13)(14)(15)(16)(17). The causes and mechanisms of early implant failure are unclear, different studies (5-11) have found a variety of statistically significant factors associated with early implant failure, these are: age and sex (11), systemic diseases (8,9), smoking (5-7,9,10), type of edentulism (8,9), maxillary implant location (6), quantity and quality of bone (5)(6)(7)(8), and implant length and diameter (7,8).…”
Section: Introductionmentioning
confidence: 99%